HS train and urban tourist attractiveness - La Rocca, Rosa Anna (TeMA - Journal of Land Use, Mobility and Environment, 2008)
This work is targeted to check how the implementation of high speed has produced physical transformations in the organization of the urban areas involved by the new connection and how those transformations have been addressed to increase tourist urban supply, in terms both of dedicated services and of location of functions contributing to increase the attractiveness of the urban area and the whole city. The tourist attractiveness of a territory is meant as the co-existence of several factors which all together make “unique” a place, giving it a characteristic of “excellence”. Through the analysis of studies and researches on the subject carried out in scientific field, we can attest that the users of high speed rail are mainly, directly or indirectly, of tourist type. This fact allows us to make hypotheses on the users typology mostly interested in the high speed rail and consequently to work out indications about the organization of urban supply for meeting that demand. The speed link between Rome and Naples connects two cities with high tourist attractiveness being substantially different. The connection between these two international tourism destinations is not to be seen in terms of competitiveness but on the contrary in relation to possible “complementarities” that the fast link could produce. As regards this last consideration, the study defines the eventual directions to define an integrated tourist territory between Rome and Naples.